Distant shores : the odyssey of Rockwell Kent / Constance Martin ; with an essay by Richard V. West. - Martin, Constance (University of California Press, 2000)
Distant Shores profiles the work of Rockwell Kent, one of the most popular American illustrators of the 20th century. Kent drew his inspiration from nature and the wilderness, and provided the illustrations for the novel Moby Dick.